Holy Scripture revelation, inspiration and interpretation - Bloesch, Donald G. 1928-2010 (Downers Grove, IL IVP, 1994)
Includes bibliographical references.
Keywords: Bible -- criticism, interpretation, etc; Bible -- evidences, authority, etc; Bible -- inspiration